2009
DOI: 10.1007/s00775-009-0492-x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the protein and solvent contributions to the reduction potentials of [4Fe–4S]2+/+ clusters: crystal structures of the Allochromatium vinosum ferredoxin variants C57A and V13G and the homologous Escherichia coli ferredoxin

Abstract: The crystal structures of the C57A and V13G molecular variants of Allochromatium vinosum 2[4Fe-4S] ferredoxin (AlvinFd) and that of the homologous ferredoxin from Escherichia coli (EcFd) have been determined at 1.05-, 1.48-, and 1.65-A resolution, respectively. The present structures combined with cyclic voltammetry studies establish clear effects of the degree of exposure of the cluster with the lowest reduction potential (cluster I) towards less negative reduction potentials (E degrees ). This is better illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Both of the two shorter Fe-Fe distances have been reported earlier: a Fe-Fe path of 2.62 Å was observed in the crystallographic models of bacterial ferredoxin, whereas a even shorter Fe-Fe path of 2.46 Å was seen in the EXAFS fits to the oxidized P-cluster of MoFe protein. 22,23 In contrast, no reasonable fits that include three Fe-Fe paths can be generated for either VnfH or AnfH consistently, resulting in a very high σ 2 value on the 2.68 Å path for VnfH (σ 2 =0.0540) and the 2.72 Å path for AnfH (σ 2 =0.0456) (Table 3), thereby effectively reducing the contribution of this path to a very minor degree. It should be noted that, although the inclusion of an extra Fe-Fe path improves the fit to the NifH EXAFS data, it does not improve the fit appreciably enough to merit its selection over the two-path fit.…”
Section: Resultsmentioning
confidence: 99%
“…Both of the two shorter Fe-Fe distances have been reported earlier: a Fe-Fe path of 2.62 Å was observed in the crystallographic models of bacterial ferredoxin, whereas a even shorter Fe-Fe path of 2.46 Å was seen in the EXAFS fits to the oxidized P-cluster of MoFe protein. 22,23 In contrast, no reasonable fits that include three Fe-Fe paths can be generated for either VnfH or AnfH consistently, resulting in a very high σ 2 value on the 2.68 Å path for VnfH (σ 2 =0.0540) and the 2.72 Å path for AnfH (σ 2 =0.0456) (Table 3), thereby effectively reducing the contribution of this path to a very minor degree. It should be noted that, although the inclusion of an extra Fe-Fe path improves the fit to the NifH EXAFS data, it does not improve the fit appreciably enough to merit its selection over the two-path fit.…”
Section: Resultsmentioning
confidence: 99%
“…YfhL is a member of the "Alvin" ferredoxin family, first identified in Allochromatium vinosum (35). These novel proteins contain two [4Fe-4S] clusters of widely differing and very low redox potential (E 0 1 ϳ Ϫ650 mV; E 0 2 ϳ Ϫ450 mV) due to unique structural motifs (36). Elsen et al found evidence that the essential Alvin ferredoxin in Pseudomonas aeruginosa was likely not involved in the catabolism of aromatic compounds but instead that its gene had the constitutive expression characteristics of a housekeeping gene (37).…”
Section: Discussionmentioning
confidence: 99%
“…49 In comparison to other designed [4Fe-4S] proteins, the reduction potential of BMC-T1-S55C is comparable to the value of -350 mV (at pH 8) reported for the minimal ferredoxin maquette 50 but significantly more positive than the value reported for the DSD-Fdm (Domain-Swapped Dimer-Ferredoxin maquette ) of -479 mV (at pH 7.5), 43 as well as the minimal photosystem I F A -and F B -maquettes of -440 mV and -470 mV (at pH 8.3), respectively 51. The similarity of the reduction potential between BMC-T1-S55C and the minimalist ferredoxin maquette may reflect the degree of solvent exposure of the clusters in both systems, whereas the more negative potential of DSM-Fdm may be due, at least in part, to the burial of the cluster in the hydrophobic core of its three-helix bundle scaffold 52. Notably, the reduction potential of BMC-T1-S55C is much lower than the value determined for the [4Fe-4S] cluster of PduT from C. freundii, +99 mV (at pH 7).…”
mentioning
confidence: 96%